The Effect of the Source of Deep Water in the Eastern Mediterranean on Western Mediterranean Intermediate and Deep Water - Amitai, Yael; Ashkenazy, Yosef; Gildor, Hezi (Frontiers in Marine Science, 2021)
The deep water in the western Mediterranean Sea was found to be significantly affected by a climatic event that took place in the eastern Mediterranean during the 1990s. Numerical simulations of the entire Mediterranean Sea showed that multiple equilibria states in the eastern Mediterranean can exist under present-day-like conditions. The two stable states that were found are associated with intermediate water exchange between the eastern Mediterranean’s Aegean and Adriatic Basins. In the first state, the Adriatic acts as a source of deep water that flows into the deep layers of the eastern Mediterranean; in the second state, there is no source of deep water in the Adriatic and the eastern Mediterranean intermediate water is warmer and saltier. We studied the water pathways, in both stable states, into the western Mediterranean and found that the eastern Mediterranean water’s properties signature can be seen as far as the Gulf of Lion, which is an important open-ocean deep water convection site. Meaning that, the eastern Mediterranean water characteristics are manifested in deep and intermediate water properties all over Mediterranean Sea. The water propagating from the eastern to the western Mediterranean also has different flow regimes, in both states, through the Sicily Strait and in the Tyrrhenian Basin, as seen from a Lagrangian analysis.